O aluno público alvo da educação especial no ensino médio: as relações entre família e escola - Muto, Jéssica Harume Dias; Campos, Juliane Ap. de Paula Perez; Melo, Eleonice Máximo e (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2016)
This qualitative study aims to analyze the family-school relationship with the participation of four mothers of Special Education Students (PAEE) enrolled in high school at a public school in the state of São Paulo. Data from semi-structured interviews were analyzed and grouped into themes: inclusion; PAEE students in regular schools; family and school; PAEE and student in high school. The results show the importance of informing the families about the educational rights that the law provides PAEE students in the process of inclusion in regular education; changes in the family-school relationship; report on the special education teacher's role within the school to families, and on the potential and limitations of PAEE students in front of the school. It considers the need to improve communication between family-school, proposing alternatives that benefit from this partnership. Thus, it was evident gaps for further research in this area.